Community behavior towards maternal and child health services during the covid-19 pandemic at tualang public health center, siak district - Dewi Sanita; Novita Rany; Doni Jepisah (Science Midwifery, 2023)
Maternal and child health (MCH) services stand as pivotal components of Public Health Centers, serving to enhance the well-being of both mothers and children. In light of this, optimizing the management of MCH programs becomes imperative. However, data from the Siak District Health Office in 2020 unveiled that the Tualang Public Health Center exhibited lower MCH program accomplishments in comparison to its counterparts within the Siak District. This study, therefore, strives to procure insights into the knowledge, attitudes, health promotion initiatives, and family backing pertinent to MCH services during the COVID-19 pandemic within the operational sphere of Tualang Public Health Center, Siak District. Employing a qualitative approach underpinned by the phenomenological method, this research involves primary informants encompassing expectant mothers and mothers of young children. Supplementary informants encompass spouses or guardians, along with key stakeholders like the Head of Tualang Public Health Center, the Responsible Party for the MCH Program, and Health Promotion Officers. The research methodology encompasses in-depth interviews and meticulous observations, followed by a data analysis fortified by source and data triangulation. Findings underscore a dearth in mothers' understanding of MCH services, juxtaposed with positive attitudes towards them. While health promotion initiatives for MCH services appear underutilized, familial support surges to its zenith. As a synthesis of these findings, it's deduced that MCH services within the operational precinct of Tualang Public Health Center, Siak District, have yet to attain optimal efficacy. In this regard, it's advocated that Tualang Public Health Center orchestrate succinct workshops or extend educational outreach to various stakeholders, including Subdistrict Heads, Village Chiefs, Religious Leaders/Tabligh Teams, District/Village PKK (Family Welfare Movement) Activators, Health Cadres, and Family Planning Field Officers.